PENERAPAN NILAI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) OLEH BAPENDA KOTA MADIUN DALAM TRANSAKSIJUAL BELI TANAH DAN BANGUNAN - Nuryanti, Dian (JURNAL ILMIAH EDUNOMIKA, 2024)
Land and Building Acquisition Duty (BPHTB) is one of the significant sources of local revenue for the Government of Madiun City. However, the implementation of BPHTB value determination in land and building sale and purchase transactions often causes problems, especially related to the transparency and accuracy of the assessment conducted by the Regional Revenue Agency (Bapenda). These obstacles can affect public trust and the efficiency of local tax administration. This study aims to analyze the application of BPHTB value by Bapenda Madiun City in land and building sale and purchase transactions. This study also aims to identify the obstacles faced and provide recommendations to improve the transparency and accuracy of BPHTB valuation. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with relevant parties, including Bapenda officers, notaries, and communities involved in land and building sale and purchase transactions. The study analyzed official documents related to the determination of BPHTB. The results show that the application of BPHTB values by Bapenda Madiun City still faces several obstacles, such as the lack of transparency in the valuation process and the difference between the market value and the value determined by Bapenda. Nevertheless, improvement efforts such as training for appraisal officers and the use of information technology in the appraisal process have begun to be implemented. This study concludes that to improve the effectiveness of BPHTB implementation in Madiun City, it is necessary to improve transparency and accuracy in the valuation process. Suggestions in the research are increasing the capacity of appraisal officers, using more sophisticated information systems, and increasing socialization to the public regarding the procedures and basis for determining BPHTB.